Sentiment Analysis Marketplaces Digital menggunakan Machine Learning - Feliks Ferianro Kiedrowsky; Andrianingsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
In the current era, in the world of technology is increasingly developing, one of which is the development of online buying and selling platforms (e-commerce). E-commerce is the performance of remote transactions of goods or services between two companies (business-to-business) or between companies and customers (business-to-consumers). E-commerce has facilitated remote transactions. The existence of this online shopping platform greatly affects the people of Indonesia and all over the world who carry out online shopping activities, especially in the current pandemic situation. There are many e-commerce platforms that we can use today. When we make purchases online, we are offered several payment methods on each of the platforms we will use. This study will discuss sentiment analysis based on a questionnaire completed by respondents. The results of this study will lead to user satisfaction using the payment system provided on the selected platform and will show the most frequently used payment system on each platform. The parameters for this search use payment system, age, occupation, and background. This study uses Naive Bayes methods and Decision Tree.